(untitled) (Research, Society and Development, 2020)
Carpooling contributes to the improvement of air quality and traffic, by reducing the emission of pollutants into the atmosphere and congestion. This work is aimed at analyzing the carpool system used by the university community of the Universidade Federal de Itajubá (Unifei), Itabira Campus. It seeks to identify the profile and the demands of passengers and drivers, as well as the reasons for using this transportation system and the average distance that each group travels to the start/end points. The work also seeks to map new start/end points and to suggest them for daily use. Results indicate that the main reason for using the system is to spend less on transportation and contribute to people who travel the same route. Eleven different routes and twenty new start/end points were presented by the interviewees. As a conclusion of this work, the results were used to propose four new routes